1951
DOI: 10.1002/pol.1951.120070401
|View full text |Cite
|
Sign up to set email alerts
|

A study of the oxidative degradation of polyvinyl formal

Abstract: The investigation of the thermal degradation or pyrolysis of vinyl polymers has been pursued from the theoretical and the experimental standpoint for polystyrene,' polymethyl methacrylate,2 and polythene.3 The degradation of the first two polymers seems to be predominantly a depolymerization, while that of polythene is a process of random chain scission. The methods have been weight loss, viscosity studies, molecular weight distribution, osmotic measurements, and infrared analysis. The oxidative degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1960
1960
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 6 publications
(2 reference statements)
0
21
0
Order By: Relevance
“…One characteristic of this process is an increasing carbonyl content which is detected by infrared spectroscopy. A free-radical mechanism for the oxidation of poly(vinyl formal) has been proposed by Beachell et al [7]. PVB can also decompose by a cyclic-elimination mechanism to release butyraldehyde, with associated chain breakage to leave aldehyde and unsaturated end-groups (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One characteristic of this process is an increasing carbonyl content which is detected by infrared spectroscopy. A free-radical mechanism for the oxidation of poly(vinyl formal) has been proposed by Beachell et al [7]. PVB can also decompose by a cyclic-elimination mechanism to release butyraldehyde, with associated chain breakage to leave aldehyde and unsaturated end-groups (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Sacks and co-workers [5,6] have recently completed similar studies on the decomposition chemistry of ceramic green bodies containing PVB. Decomposition of the related polymer poly-(vinyl formal) has been studied by Beachell et al [7], who found that formaldehyde production was responsible for about 25% of the weight loss at 150 ° C. They proposed an oxidative mechanism for the formation of formaldehyde. Changes observed in the infrared spectrum of the polymer included loss of the formal and C-H bands, an early increase in the intensity of the carbonyl band, and the subsequent formation of C=C bands at 1612 and 910cm -1 .…”
Section: Ch3mentioning
confidence: 98%
“…These attributions were consistent with the earlier infrared results by Beachell et a1. 16 and Chanda et al17 (see Discussion later).…”
Section: Pvf Adhesivementioning
confidence: 81%
“…Thermogravimetric analysis indicates significant rate of weight loss, starting about 240 • C in air or about 320 • C in nitrogen for PVF (63,64) compared to about 280 • C in air or up to about 320 • C in nitrogen for PVB (65). In air, significant oxidative degradation occurs at lower temperatures with longer thermal exposure as evidenced by loss of solubility, color development, and increasing T g attributed to the initial formation of unsaturated bonds and cross-linking (64,66). Mechanisms for degradation have also been studied employing combination techniques, including gas chromatography/mass spectrometry and infrared spectroscopy/thermogravimetry (65,67).…”
Section: Propertiesmentioning
confidence: 99%